English Students’ Perspective On English Class Performance In Universitas Bhinneka PGRII - Nugrahini, Yulia; Rakhmawati, Ika; Wijatmoko, Irvan (Universitas Pahlawan Tuanku Tambusai, 2024)
English class performance is an event that is held by the English Language Study Program at the Universitas Bhinneka PGRI. This event is held regularly every year, since 2018 initiated by a student of Universitas Bhinneka PGRI Tulungagung, Plosokandang - Tulungagung City itself, namely by (Siti Rochimah, 2020). This study aims to examine the perspective of students on the existence of English Class Performance. This type of research is Qualitative Research using data collection methods through a questionnaire to answer how the second, fourth and sixth semester students' perspectives on English Class Performance events. So that data will be obtained about their perspectives in depth and can be used as reference considerations both for the committee and for the English study program later. The instrument used in this study used a questionnaire method and direct interviews with the chairpersons of each class (session) as well as the creator of the idea of an English Class Performance event to obtain accurate information about history and how the origins of English class performance were formed. To obtain the validity of the data in this study carried out by triangulation of sources or easier matching between one source with another source or next researcher. Based on the results of the research analysis, it can be concluded that English Class Performance is an event that is very useful for students of English study programs, especially for implementing or applying knowledge gained while in class directly and this event is very useful for students to train their mentality to perform directly speak English both formal and informal in public.